2017
DOI: 10.3390/molecules22030455
|View full text |Cite
|
Sign up to set email alerts
|

The Formyl Peptide Receptors: Diversity of Ligands and Mechanism for Recognition

Abstract: The formyl peptide receptors (FPRs) are G protein-coupled receptors that transduce chemotactic signals in phagocytes and mediate host-defense as well as inflammatory responses including cell adhesion, directed migration, granule release and superoxide production. In recent years, the cellular distribution and biological functions of FPRs have expanded to include additional roles in homeostasis of organ functions and modulation of inflammation. In a prototype, FPRs recognize peptides containing N-formylated met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
218
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(230 citation statements)
references
References 227 publications
(290 reference statements)
5
218
0
7
Order By: Relevance
“…Formyl peptide receptors (FPRs) are G protein-coupled receptors (GPCR) that play an important role in leukocyte activation and chemotaxis [1]. In humans, there are three FPR isoforms: FPR1, FPR2, and FPR3 [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Formyl peptide receptors (FPRs) are G protein-coupled receptors (GPCR) that play an important role in leukocyte activation and chemotaxis [1]. In humans, there are three FPR isoforms: FPR1, FPR2, and FPR3 [1].…”
Section: Introductionmentioning
confidence: 99%
“…In humans, there are three FPR isoforms: FPR1, FPR2, and FPR3 [1]. FPR1 is expressed on a variety of cell types, including neutrophils, macrophages, natural killer (NK) cells, immature dendritic cells, astrocytes, microglial cells, hepatocytes, and bone marrow-derived mesenchymal stem cells [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later studies have revealed that mitochondrial NFPs are recognized by high-affinity formyl peptides receptors (FPRs) (Dahlgren et al, 2016). FPRs constitute a small group of 7-transmembrane domain, G-protein-coupled receptors that are expressed not only on neutrophils, monocytes and dendritic cells but also on hepatocytes, endothelial cells and cells of the nervous system (He and Ye, 2017). Indeed, a recent study has suggested a pathogenic role of mitochondrial NFPs in human disease (Dorward et al, 2017).…”
Section: Inflammation and Mitochondriamentioning
confidence: 99%
“…neutrophils, macrophages, dendritic cells) but also found in endo-and epithelial cells [62]. A broad range of FPR1 ligands, both agonist and antagonists, have been described [63], and autocrine/paracrine signalling of externalized AnxA1 protein and/or its peptides via the FPRs might explain its wellknown immune-modulatory and pro-resolving actions. Upregulation of AnxA1 expression is observed in several inflammatory conditions [64] and thought to function in resolution and tissue protection [65].…”
Section: Extracellular Functions-annexins As Ligands Of Defined Inflamentioning
confidence: 99%